"Don't Be Too Polite Girls": Gender Hierarchies and Women's Leadership in the Meatworkers' Union in the 1970s. (1st November 2022) - Willis, Freya
Abstract : Women's exclusion from the workforce and trade union movement has historically been legitimated not only through policies such as pay discrimination or restrictions on the kinds of work women can perform, but also through constructed notions of masculinity and femininity. In the Australian meat industry and the Australasian Meat Industry Employees' Union (AMIEU), women were excluded from the masculinist culture which valued physical strength, mateship, and solidarity above all else and marginalised by reference to domestic and sexual tropes. In the 1970s, this culture came under attack from female meatworkers and the Women's Liberation Movement, who shared a vision to free women from subordinate gender roles. Drawing on archival material and oral history interviews, this article examines the construction of gender hierarchies in the meat industry and AMIEU, and how women in the 1970s challenged these to forge new modes of leadership.